Analisis Strategi Bauran Pemasaran Aplikasi Online Klik Indomaret Dalam Meningkatkan Penjualan di Era Global Bisnis - Puspita Ayunda Zahra; Zulkifli (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This research aims to analyze the Marketing Mix Strategy of the Klik Indomaret Online Application in increasing sales in the global business era and the obstacles encountered in the implementation of the digital marketing strategy at Indomaret Telaga Murni. This research employs a qualitative descriptive method. Data were collected through documentation, interviews, and observation. The findings show that the marketing strategy of the Klik Indomaret online application at Telaga Murni is carried out using the 7P marketing mix approach (product, price, promotion, place, people, process, and physical evidence). Over the past three years (2022–2025), sales through the Klik Indomaret Telaga Murni application have declined.This decline is influenced by various obstacles, particularly technical issues in application performance, such as slow access, frequent errors, reduced promotional activities on the application, and a suboptimal user experience. To overcome these challenges, several strategic solutions are required, including strengthening servers and networks, simplifying the application interface to be more user-friendly, adding interactive features to enhance communication withconsumers, and providing digital training for store teams to improve service quality. With the implementation of these solutions, the marketing strategy through the online application is expected to be more optimalized in increasing sales. Keywords: Perception of Convenience; Perception of Benefits, Interest In Use